Carbon black with high conductivity, preparation method, device and electrode, and secondary battery thereof

By forming multi-layer graphene-like graphene-like sheet protrusions on the surface of the sphere of carbon black, the problems of poor dispersion of linear conductive materials and complex graphene preparation are solved, and high-conductivity and low-cost carbon black materials are achieved, which significantly improves the performance of electrodes and batteries.

CN117701035BActive Publication Date: 2025-04-25JIAOZUO CITY HEXING CHEMICAL INDUSTRY CO LTD

Patent Information

Application Number
CN202311792302.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-25
Publication Date
2025-04-25
Estimated Expiration
2043-12-25

AI Technical Summary

Technical Problem

In the prior art, linear conductive materials are difficult to disperse uniformly in the electrode slurry, resulting in poorer uniformity of electrode resistance; at the same time, the preparation process of graphene is complex and costly, and when the thickness is large or the plane size is too large, it will hinder the movement of the electrolyte, resulting in deterioration of battery performance.

Method used

A carbon black with high conductivity is provided, with an average particle size of 20 to 40 nm, including a sphere and a graphene-like sheet protrusion located on the surface of the sphere. The thermocleavage reaction of acetylene and methane in a hydrogen-containing environment was adjusted to regulate the molar ratio of H to C to be >1, and a graphene-like sheet protrusion with multi-layer graphene was formed.

Benefits of technology

The carbon black can significantly improve the conductivity, improve the conductivity of the electrode and the battery performance, and at the same time, the preparation method is simple and the production cost is low.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117701035B_ABST
    Figure CN117701035B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of carbon black materials, and in particular to a carbon black with high conductivity and a preparation method, equipment, electrode, and secondary battery thereof. The carbon black with high conductivity has an average particle size of primary particles of 20 to 40 nm; the primary particles of the carbon black include a sphere and graphene-like sheet protrusions on the surface of the sphere. The carbon black of the present invention has graphene-like sheet protrusions on the surface of the sphere, and has the characteristics of carbon black and graphene, and can form point-to-surface contact between primary particles or between particles of electrode materials, thereby improving the conductivity, and can significantly improve the conductivity of the slurry and the electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of carbon black materials, and in particular to a carbon black with high conductivity and a preparation method, equipment, electrode and secondary battery thereof. Background Art

[0002] Conductive materials are generally added to the positive and / or negative electrodes of lithium-ion secondary batteries to improve conductivity. Usually, point-type conductive materials, such as carbon black, are mainly added to the electrodes; at the same time, linear conductive materials, such as carbon nanotubes, carbon nanofibers, etc., can also be added to further improve the conductivity of the electrodes.

[0003] However, although linear conductive materials have excellent conductivity, they are generally bundle-shaped and / or tangled, so they are not easy to be evenly dispersed in the electrode slurry, which leads to poor uniformity of electrode resistance. In order to solve the dispersibility problem, functional groups can be introduced into linear conductive materials. However, the introduction of functional groups may cause side reactions on the surface of the conductive material, making it difficult to achieve large-scale application in batteries.

[0004] At the same time, graphene has excellent electrical conductivity and can be used as a planar conductive material. However, the preparation process of single-layer graphene with high electrical conductivity is difficult and the production cost is high. When the thickness of graphene is greater than a certain level or the plane size is too large, there will be a problem that too much surface contact of graphene prevents the movement of electrolyte in the electrode, thereby causing the deterioration of battery performance.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The purpose of the present invention is to provide carbon black with high conductivity and its preparation method, equipment, electrode and secondary battery. The carbon black of the present invention has the characteristics of both carbon black and graphene, can significantly improve the conductivity, and the preparation method is simple.

[0007] In order to achieve the above-mentioned object of the present invention, the present invention provides a carbon black with high conductivity, wherein the average particle size of the primary particles of the carbon black is 20 to 40 nm;

[0008] The primary particles of the carbon black include a sphere and graphene-like protrusions located on the surface of the sphere.

[0009] In a specific embodiment of the present invention, the graphene-like sheet protrusions are multilayer graphene. Further, the number of layers of the multilayer graphene is ≤10, such as 2 to 8 layers.

[0010] In a specific embodiment of the present invention, the maximum value of the distance between any two points in the graphene-like sheet protrusion is 10 to 50 nm.

[0011] In a specific embodiment of the present invention, the carbon black is acetylene black.

[0012] In a specific embodiment of the present invention, the graphene-like sheet protrusions are in-situ grown on the surface of the sphere.

[0013] In a specific embodiment of the present invention, the BET specific surface area of ​​the carbon black is 65 to 180 m 2 / g; DBP oil absorption value is 235~375cm 3 / 100g.

[0014] In a specific embodiment of the present invention, the carbon black has a Raman spectrum at 2648-2660 cm -1 The full width at half maximum of the 2D Raman scattering peak in the range of 80 to 90 cm -1 ; The ratio of the peak intensity of the 2D Raman scattering peak to the peak intensity of the G Raman scattering peak is 0.55 to 0.87. Further, the Raman crystallite plane size of the carbon black is

[0015] In a specific embodiment of the present invention, the crystallinity of the carbon black is 42% to 52%, such as 46% to 52%.

[0016] In a specific embodiment of the present invention, the powder resistivity of the carbon black is 0.13 to 0.206 Ω / cm.

[0017] Another aspect of the present invention provides a method for preparing any one of the above-mentioned carbon blacks, comprising the following steps:

[0018] Acetylene and methane undergo thermal cracking reaction in a hydrogen-containing and air-isolated environment to form carbon black;

[0019] The flow rates of acetylene, methane and hydrogen are regulated so that the molar ratio of H to C in the thermal cracking reaction zone is greater than 1.

[0020] In a specific embodiment of the present invention, the molar ratio of H to C in the thermal cracking reaction zone is 2 to 3.

[0021] In a specific embodiment of the present invention, the gas flow directions of the acetylene and the methane are opposite, and the gas flow direction of the hydrogen is arranged at an angle to the gas flow directions of the acetylene and the methane. Further, the angle is 45° to 60°.

[0022] Another aspect of the present invention provides an apparatus for implementing any one of the above-mentioned methods for preparing carbon black, comprising: a cracking furnace body, a reaction chamber formed inside the furnace body;

[0023] The cracking furnace body is provided with two nozzles communicating with the reaction chamber, and the cracking furnace body is formed with a furnace head corresponding to the two nozzles; the furnace head is provided with at least one gas introduction pipe communicating with the reaction chamber;

[0024] The two nozzles include a first nozzle and a second nozzle.

[0025] In a specific embodiment of the present invention, two gas introduction pipes are included, and the two gas introduction pipes are arranged opposite to each other on both sides of the furnace head.

[0026] In a specific embodiment of the present invention, the central axis of the gas introduction pipe is arranged at an angle with the central axis of the furnace head, and further, the angle is 30° to 45°.

[0027] Another aspect of the present invention provides an electrode, comprising any one of the carbon blacks described above.

[0028] Another aspect of the present invention provides a secondary battery, comprising a positive electrode, a negative electrode, an electrolyte and a separator; at least one of the positive electrode and the negative electrode is any one of the electrodes described above.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] (1) The carbon black of the present invention has graphene-like protrusions on the surface of the sphere, and has the characteristics of both carbon black and graphene, and can form point-to-surface contact between primary particles or with electrode material particles, thereby improving the conductivity and significantly improving the conductivity of the slurry and the electrode;

[0031] (2) The method for preparing carbon black of the present invention has a simple process and a relatively low production cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0033] Figure 1 A schematic diagram of the structure of an apparatus for preparing highly conductive carbon black provided in an embodiment of the present invention;

[0034] Figure 2 A schematic top view of a nozzle and a furnace head provided in an embodiment of the present invention;

[0035] Figure 3 This is a transmission electron microscope image of the carbon black prepared in Example 1 of the present invention;

[0036] Figure 4 for Figure 3 A partial magnified view of the transmission electron microscope image;

[0037] Figure 5 for Figure 3 Another partial enlarged view of the transmission electron microscope image;

[0038] Figure 6 The Raman spectrum of the carbon black prepared in Example 1 of the present invention;

[0039] Figure 7 The Raman spectrum of the carbon black prepared in Example 2 of the present invention;

[0040] Figure 8 This is the Raman spectrum of the carbon black prepared in Example 3 of the present invention.

[0041] Reference numerals:

[0042] 10-cracking furnace body; 11-reaction chamber; 12-furnace head;

[0043] 13-nozzle; 14-gas inlet pipe; 15-discharge port;

[0044] 131 - first nozzle; 132 - second nozzle. DETAILED DESCRIPTION

[0045] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0046] Carbon black is a commonly used conductive material widely used in many industries, such as the field of secondary batteries. With the development requirements of the battery field, it is necessary to further improve the conductive properties of carbon black.

[0047] In one aspect, the present invention provides carbon black with high conductivity, wherein the average particle size of primary particles of the carbon black is 20 to 40 nm;

[0048] The primary particles of carbon black include a sphere and graphene-like protrusions on the surface of the sphere.

[0049] The carbon black of the present invention has graphene-like protrusions formed on the surface of the sphere, and the graphene-like protrusions on the surface of the sphere are similar to solar prominences. The carbon black of the present invention has both a carbon black core sphere and graphene-like protrusions, so that it has the characteristics of both carbon black and graphene, and can form point-to-surface contact between primary particles or between electrode material particles, thereby improving the conductivity, which has obvious advantages over the point-to-point contact of traditional carbon black.

[0050] For example, in different embodiments, the average particle size of the primary particles of the carbon black of the present invention can be 20 nm, 25 nm, 28 nm, 30 nm, 32 nm, 35 nm, 38 nm, 40 nm or a range consisting of any two thereof.

[0051] It should be noted that the primary particles of the carbon black of the present invention are roughly spherical, and the average particle size of the primary particles of the carbon black is a value obtained by averaging the particle sizes measured using photographs taken with a transmission electron microscope, etc. In addition, the particle size is a circle equivalent diameter calculated from the area of ​​the primary particles.

[0052] In a specific embodiment of the present invention, the graphene-like sheet protrusions are multilayer graphene. Further, the number of layers of the multilayer graphene is ≤ 10, such as 2 to 8 layers.

[0053] The graphene-like sheet protrusions of the present invention are multilayer graphene, and the number of layers of the multilayer graphene can be ≤10, ≤8, ≤5, ≤4, etc. Specifically, the number of layers of the multilayer graphene can be 2 layers, 3 layers, 4 layers, 5 layers, 6 layers, 7 layers, 8 layers or a range consisting of any two of them.

[0054] The number of graphene-like sheet protrusions on the surface of the sphere of the present invention is ≥1, such as 1, 2, 3, 4, etc., and the specific number is not limited; when the number of graphene-like sheet protrusions located on the surface of the sphere is ≥2, the number of multilayer graphene layers of each graphene-like sheet protrusion can be independently selected from 2 to 8 layers, and can be the same or different.

[0055] When the number of multilayer graphene of the graphene-like sheet protrusions on the surface of the sphere meets the above requirements, the unique flexibility of the graphene sheet can be demonstrated, and the surface contact between the graphene-like sheet protrusions and between the graphene-like sheet protrusions and the carbon black sphere can be improved, thereby improving conductivity.

[0056] In a specific embodiment of the present invention, the maximum value of the distance between any two points in the graphene-like sheet protrusion is 10 to 50 nm.

[0057] For example, in different embodiments, the maximum value of the distance between any two points in the graphene-like sheet protrusion can be 10nm, 20nm, 30nm, 40nm, 50nm, or a range consisting of any two thereof. Wherein, the maximum value of the distance between any two points refers to the length L of the largest line segment between one point and another point in the graphene-like sheet protrusion observed by transmission electron microscopy (TEM). In addition, the above maximum value refers to the average value of L of 100 graphene-like sheet protrusions observed by TEM.

[0058] In actual operation, the maximum value of the distance between any two points in a specific graphene-like sheet protrusion can be controlled by regulating the thermal cracking process, such as by adjusting the flow rate of methane and hydrogen. The maximum value of the distance between any two points in the graphene-like sheet protrusion of the present invention is much smaller than that of ordinary graphene. Since the graphene-like sheet protrusion has a smaller size, it can effectively reduce the resistance of the electrolyte solution to the movement in the electrode, significantly reduce the ion barrier effect, and improve the smoothness of the diffusion of ions in the electrolyte in the electrode.

[0059] In a specific embodiment of the present invention, the carbon black is acetylene black.

[0060] In a specific embodiment of the present invention, graphene-like sheet protrusions are in-situ grown on the surface of the sphere.

[0061] Graphene-like protrusions are formed on the surface of the sphere by in-situ growth, which ensures the stability of the bonding of the graphene-like protrusions in the primary particles to the surface of the sphere and further improves the conductivity.

[0062] In a specific embodiment of the present invention, the BET specific surface area of ​​carbon black is 65 to 180 m 2 / g; DBP oil absorption value is 235~375cm 3 / 100g.

[0063] The BET specific surface area is tested according to the method of GB / T19587-2004. The more developed the microporous structure is, the larger the BET specific surface area is, that is, the BET specific surface area can reflect the development of the porous structure of carbon black. The BET specific surface area of ​​the carbon black of the present invention can be 65m 2 / g, 85m 2 / g、100m 2 / g, 120m 2 / g, 140m 2 / g, 150m 2 / g, 160m 2 / g, 180m 2 / g or the range of any two of them, and the BET specific surface area is within the above range, which indicates that the carbon black has a developed porous structure, which increases the number of contact points with other substances (such as active substances in the electrode) and can give full play to the conductivity of the carbon black; at the same time, due to its percolation effect in the electrode material, it has a high conductivity imparting ability.

[0064] The DBP oil absorption value is determined by the standard method of "GB / T 3780.2-2017 Carbon Black Part 2: Determination of Oil Absorption Value". The DBP oil absorption value is used to characterize the void volume inside the carbon black aggregate. The larger the void volume of the carbon black aggregate, the larger its DBP oil absorption value, which means that the chain branch structure of the carbon black is more developed. The DBP oil absorption value of the carbon black of the present invention can be 235cm 3 / 100g、250cm 3 / 100g、280cm 3 / 100g、300cm 3 / 100g、320cm 3 / 100g、340cm 3 / 100g、350cm 3 / 100g、375cm 3 / 100g or the range of any two thereof, and the DBP oil absorption value is within the above range, indicating that the carbon black of the present invention has a developed conductive network.

[0065] In a specific embodiment of the present invention, carbon black has a Raman spectrum at an excitation wavelength of 532 nm at 2648-2660 cm -1 The full width at half maximum of the 2D Raman scattering peak in the range of 80 to 90 cm -1 ; The ratio of the peak intensity of the 2D Raman scattering peak to the peak intensity of the G Raman scattering peak is 0.55 to 0.87. Furthermore, the Raman crystallite plane size of carbon black is

[0066] The specific Raman spectrum test method and test parameters are as follows:

[0067] Using a laser Raman spectrometer, several particles of the carbon black sample to be tested were placed on a glass slide and scraped several times with a spatula to make it flat. The test was carried out under the following test conditions: YAG laser (excitation wavelength): 532nm, number of lines: 600gr / mm, filter: D0.6, objective lens magnification: 100x, exposure time: 150 seconds, and accumulation times: 2 times.

[0068] Raman spectroscopy can reflect the number of graphene layers, stacking mode, edge structure, etc. in the graphene-like protrusions in carbon black. The Raman spectrum of graphene is composed of several peaks, mainly G Raman scattering peak, D Raman scattering peak and 2D Raman scattering peak. Among them, the G Raman scattering peak is caused by the in-plane vibration of sp2 carbon atoms; the D Raman scattering peak is the disordered vibration peak of graphene, which can reflect the structural defects or edges in the graphene sample; the 2D Raman scattering peak is the second-order Raman peak of double phonon resonance, which can reflect the interlayer stacking mode of carbon atoms in the graphene sample; the G Raman scattering peak intensity and the peak shape of the 2D Raman scattering peak can reflect the number of graphene layers. In addition to the different peak shapes of the 2D Raman scattering peak, the intensity of the G Raman scattering peak of the Raman spectra of graphene with different numbers of layers will also increase approximately linearly with the increase of the number of layers.

[0069] The Raman spectrum of carbon includes a wavelength of about 1340 cm -1 and 1580cm -1 There are two main "resonance" bands at the center, denoted as "D" and "G" bands. The Raman crystallite plane size (La) is measured by Raman spectroscopy, and regression analysis yields the following empirical relationship: La = 43.5 × (area of ​​G band / area of ​​D band), where La is calculated in angstroms. The crystal domains of carbon black can be characterized by La, which can give an indication of the degree of graphitization. The higher the La value, the higher the degree of graphitization.

[0070] For example, in different embodiments, in the Raman spectrum of carbon black with an excitation wavelength of 532 nm, the peak position range of the 2D Raman scattering peak can be selected from but not limited to 2648 cm -1 、2650cm -1 、2652cm -1 、2655cm -1 、2658cm -1 、2660cm -1 or any two thereof; the full width at half maximum Δ2D corresponding to the 2D Raman scattering peak can be selected from but not limited to 80 cm -1 、81cm -1 、82cm -1 、83cm -1 、84cm -1 、85cm -1 、86cm -1 、87cm -1 、88cm -1 、89cm -1 、90cm -1 Or the range of any two of them; The peak intensity of the 2D Raman scattering peak (I 2D ) and the peak intensity of the G Raman scattering peak (I G ) ratio I 2D / I GThe Raman crystallite plane size of carbon black can be selected from but not limited to 0.55, 0.60, 0.63, 0.68, 0.70, 0.75, 0.80, 0.85, 0.87 or any two thereof; the Raman crystallite plane size of carbon black can be selected from but not limited to Or a range consisting of any two of them.

[0071] Through in-depth research, the inventors found that when the Raman spectrum of carbon black meets the above conditions, the graphene-like protrusions on the surface of the sphere have a suitable stacking method and number of layers, etc., thereby further improving the conductivity of the carbon black.

[0072] In a specific embodiment of the present invention, the crystallinity of the carbon black is 42% to 52%, such as 46% to 52%.

[0073] For example, in different embodiments, the crystallinity of carbon black may be 42%, 45%, 46%, 48%, 50%, 52%, or a range consisting of any two thereof.

[0074] The crystallinity of carbon black can reflect its degree of graphitization, which is measured from Raman spectroscopy as the ratio of the intensity of the G band to the sum of the intensities of the G band and the D band (I G / I G+D ) is obtained. A higher degree of graphitization further improves the conductivity, and when used as a conductive material for a battery, it can improve the battery capacity, etc.

[0075] In a specific embodiment of the present invention, the powder resistivity of carbon black is 0.13 to 0.206 Ω / cm.

[0076] For example, in different embodiments, the powder resistivity of carbon black may be 0.13Ω / cm, 0.14Ω / cm, 0.15Ω / cm, 0.16Ω / cm, 0.18Ω / cm, 0.20Ω / cm, 0.206Ω / cm, or a range consisting of any two thereof.

[0077] The powder resistivity is tested by a semiconductor powder resistivity tester (model FZ-2006), and the test sample is prepared by using a mold under a pressure of 83.5KG. The carbon black of the present invention has a certain structure, a suitable graphene-like protrusion morphology and a graphitization degree, which can further reduce the powder resistivity of the carbon black and improve the conductivity.

[0078] Another aspect of the present invention provides a method for preparing any one of the above carbon blacks, comprising the following steps:

[0079] Acetylene and methane undergo thermal cracking reaction in a hydrogen-containing and air-isolated environment to form carbon black;

[0080] The flow rates of acetylene, methane and hydrogen are regulated so that the molar ratio of H to C in the thermal cracking reaction zone is greater than 1.

[0081] The method for preparing carbon black of the present invention comprises the following steps: acetylene is thermally cracked to generate nucleation cores of acetylene black and the nucleation cores grow; at the same time, the heat generated by the thermal cracking of acetylene causes methane to be cracked and nucleated to grow, and a certain amount of hydrogen atoms are generated; in addition, hydrogen is supplied at the same time, so that the reaction zone has abundant hydrogen atoms, and the abundant hydrogen atoms are combined with the dangling bonds at the edges of the surface carbon clusters of the acetylene black, so as to slow down and prevent the curling and closing of the carbon clusters to form the spherical surface of the acetylene black, thereby forming graphene-like sheet protrusions on the spheres of the acetylene black.

[0082] In a specific embodiment of the present invention, the molar ratio of H to C in the thermal cracking reaction zone is 2 to 3.

[0083] For example, in different embodiments, the molar ratio of H to C in the thermal cracking reaction zone can be 2, 2.2, 2.5, 2.8, 3, or any two thereof. By regulating the molar ratio of H to C in the thermal cracking reaction zone within the above range, the reaction zone is made into a hydrogen-rich environment, further promoting the formation of graphene-like protrusions.

[0084] In actual operation, the flow rates of acetylene, methane and hydrogen can be adjusted so that the molar ratio of H to C in the thermal cracking reaction zone meets the corresponding conditions. For example, the flow rate ratio of acetylene, methane and hydrogen can be 10:5: (4.6-17.3).

[0085] In a specific embodiment of the present invention, the gas flow directions of acetylene and methane are opposite; the gas flow direction of hydrogen is arranged at an angle to the gas flow directions of acetylene and methane.

[0086] By adjusting the gas flow direction of hydrogen, acetylene and methane to form a certain angle, the acetylene black generated by the cracking of acetylene and methane can pass through the reaction zone quickly, avoiding the existence of a reflux zone to terminate the reaction, and further promoting the formation of graphene-like protrusions on the acetylene black spheres.

[0087] In a specific embodiment of the present invention, the angle is 45° to 60°, such as 45°, 48°, 50°, 52°, 55°, 58°, 60° or a range consisting of any two thereof.

[0088] In actual operation, acetylene gas and air can be introduced into the system in advance, and first burned to raise the temperature of the reaction zone to about 850°C (the temperature at which thermal cracking can occur). Then, after stopping the introduction of air for a period of time, the environmental system is isolated from the air, and then acetylene and methane are subjected to thermal cracking reaction in an environment containing hydrogen and isolated from air.

[0089] Another aspect of the present invention provides an apparatus for implementing any one of the above-mentioned methods for preparing carbon black, such as Figure 1As shown, it comprises: a cracking furnace body 10, wherein a reaction chamber 11 is formed inside the cracking furnace body for performing a thermal cracking reaction. The cavity structure of the reaction chamber 11 can be adapted to the structure of the cracking furnace body 10.

[0090] The cracking furnace body 10 is provided with two nozzles 13 connected to the reaction chamber 11 for introducing gas into the reaction chamber 11. The two nozzles 13 can extend into the reaction chamber 11 so as to introduce gas into the reaction chamber 11 to ensure the smooth progress of the thermal cracking reaction.

[0091] The cracking furnace body 10 is formed with a furnace head 12 arranged corresponding to the two nozzles 13 ; the furnace head 12 is provided with at least one gas introduction pipe 14 communicating with the reaction chamber 11 for introducing hydrogen into the reaction chamber 11 .

[0092] like Figure 2 As shown, the two nozzles 13 include a first nozzle 131 and a second nozzle 132. The first nozzle 131 is used to introduce air or methane into the reaction chamber 11, and the second nozzle 132 is used to introduce acetylene into the reaction chamber 11. The first nozzle 131 and the second nozzle 132 are arranged on opposite sides of the furnace head 12 and close to one end of the furnace head 12, and the central axis of the first nozzle 131 and the second nozzle 132 is perpendicular to the central axis of the furnace head 12. The spray directions of the first nozzle 131 and the second nozzle 132 are opposite.

[0093] In actual operation, air can be introduced through the first nozzle 131, and acetylene gas can be introduced through the second nozzle 132 to make them burn and heat up to a certain temperature (such as 850°C) to preheat the cracking furnace; then after cutting off the air supply for a period of time, methane gas is supplied from the first nozzle 131, and hydrogen is introduced through the gas inlet pipe 14 to cause a thermal cracking reaction, and the carbon black is collected after cooling.

[0094] In a specific embodiment of the present invention, two gas introduction pipes 14 are included. The two gas introduction pipes 14 are arranged opposite to each other on both sides of the furnace head 12 .

[0095] In actual operation, the cracking furnace body 10 may be provided with conventional heating components and temperature control components.

[0096] In a specific embodiment of the present invention, the central axis of the gas inlet pipe 14 is arranged at an angle with the central axis of the furnace head 12. Further, the angle is 30° to 45°. In subsequent specific embodiments, if no additional description is given, the angle is 40°, but it is not limited thereto.

[0097] By adjusting the angle between the central axis of the gas inlet pipe 14 and the central axis of the furnace head 12, the acetylene black generated by the cracking of acetylene and methane can quickly pass through the reaction zone, avoiding the existence of a reflux zone to terminate the reaction, and further promoting the formation of graphene-like sheet protrusions on the acetylene black spheres.

[0098] In a specific embodiment of the present invention, the cracking furnace body 10 further includes a discharge port 15 , which is disposed at one end of the reaction chamber 11 away from the furnace head 12 . When the reaction is completed, the carbon black leaves the reaction chamber 11 through the discharge port 15 .

[0099] In a specific embodiment of the present invention, the cracking furnace body 10 further includes a heater (not shown), and the heating method of the heater is induction heating or resistance heating, etc., but not limited thereto. The heater is used to heat the reaction zone of the reaction chamber 11 to maintain the smooth progress of the cracking reaction.

[0100] Another aspect of the present invention provides an electrode, comprising any one of the above-mentioned carbon blacks.

[0101] Among them, carbon black is used as a conductive material in the preparation of electrodes. Carbon black can be used as the only conductive material or together with other conductive materials.

[0102] Another aspect of the present invention provides a secondary battery, comprising a positive electrode, a negative electrode, an electrolyte and a separator; at least one of the positive electrode and the negative electrode is any one of the above electrodes.

[0103] The positive electrode active material or the negative electrode active material can be adjusted according to actual needs and is not limited to a certain type. The following embodiments are illustrated by only one active material, rather than limiting the type of active material.

[0104] Examples 1 to 3

[0105] Examples 1 to 3 provide methods for preparing carbon black having high conductivity, using Figure 1 The equipment shown is prepared, comprising the following steps:

[0106] (1) Acetylene gas is heated at 10 Nm 3 / h flow rate and air at 60Nm 3 / h flow rate is introduced into the cracking furnace 10 to make it burn and heat up to 850°C to preheat the cracking furnace body 10; wherein, air is supplied through the first nozzle 131 and acetylene is supplied through the second nozzle 132.

[0107] (2) Continue to supply acetylene through the second nozzle 132, and cut off the air supply for a period of time to ensure that the cracking furnace is isolated from the air. Then, the heater is heated, and methane gas is supplied from the first nozzle 131. Hydrogen is supplied through the gas inlet pipe 14. The molar ratio of H to C in the reaction chamber 11 is controlled to be 2 to 3. After the thermal cracking reaction is carried out in the reaction chamber 11, the produced carbon black is collected after cooling.

[0108] In the preparation methods of Examples 1 to 3, in step (2), the flow rates of acetylene gas, methane gas and hydrogen are shown in Table 1.

[0109] Table 1 Flow information

[0110] serial number <![CDATA[Acetylene (Nm 3 / h)]]> <![CDATA[Methane (Nm 3 / h)]]> <![CDATA[Hydrogen (Nm 3 / h)]]> H / C (molar ratio) Example 1 10 5 4.6 2 Example 2 10 5 11 2.5 Example 3 10 5 17.3 3

[0111] Example 4

[0112] This embodiment provides a method for preparing an electrode slurry, comprising the following steps:

[0113] The positive electrode active materials LiCoO2, polyvinylidene fluoride and carbon black were weighed in a mass ratio of 96:2:2, and mixed evenly in an appropriate amount of N-methylpyrrolidone to obtain an electrode slurry; wherein the carbon black in each electrode slurry is the carbon black obtained in Examples 1 to 3, and the corresponding electrode slurries are numbered as Example 4-1, Example 4-2, and Example 4-3, respectively.

[0114] Comparative Example 1

[0115] Comparative Example 1 provides a commercially available carbon black (SP).

[0116] Comparative Example 1 also provides an electrode slurry, which is prepared by referring to the method of Example 4, except that the carbon black therein is replaced by an equal weight of commercially available carbon black SP.

[0117] Comparative Example 2

[0118] Comparative Example 2 provides a carbon black, and the preparation method is the same as that of Example 1, except that: in step (2), no hydrogen is provided.

[0119] Comparative Example 2 also provides an electrode slurry, which is prepared by referring to the method of Example 4, except that the carbon black therein is replaced with an equal weight of the carbon black of Comparative Example 2.

[0120] Experimental Example 1

[0121] Figure 3 to Figure 5 This is a transmission electron microscope image of the carbon black prepared in Example 1 of the present invention. It can be seen from the figure that the primary particles of the carbon black of the present invention are roughly spherical, and its structure includes a sphere and graphene-like sheet protrusions (similar to solar prominences) located on the sphere. Since there are graphene sheet protrusions on the surface of the carbon black sphere, the carbon black of the present invention has the characteristics of both carbon black and graphene, and can form point-to-surface contacts between the primary particles and between the electrode material particles, thereby improving the conductivity, which has obvious advantages over the point-to-point contact of the traditional conductive medium carbon black.

[0122] In addition, it can be seen from the transmission electron microscope image that the maximum distance between any two points in the graphene-like sheet protrusions is 10 to 50 nm.

[0123] Specifically, the sizes of the primary particles of carbon black in different embodiments and comparative examples, as well as if they contain graphene-like protrusions, the corresponding number of layers of graphene-like protrusions (the average number of layers of 100 graphene-like protrusions observed by transmission electron microscopy) and the maximum distance between any two points are shown in Table 2.

[0124] Table 2 Carbon black morphology information of different embodiments and comparative examples

[0125]

[0126] As can be seen from Table 2, the average particle size of the primary particles of the carbon black of the present invention is 20-40 nm, the number of layers of multilayer graphene in the graphene-like sheet protrusions is ≤10, and the maximum distance between any two points in the graphene-like sheet protrusions is 10-50 nm. Its structural characteristics give it obvious advantages over the point-to-point contact of traditional conductive medium carbon black.

[0127] Experimental Example 2

[0128] Raman spectroscopy test was carried out on the carbon black of different embodiments and comparative examples. The specific test method is: using a laser Raman spectroscopy device, several particles of the carbon black sample to be tested are placed on a glass slide, and scraped with a spatula for several times to make it flat, and the test is carried out under the following test conditions: YAG laser (excitation wavelength): 532nm, number of lines: 600gr / mm, filter: D0.6, objective lens magnification: 100 times, exposure time: 150 seconds, cumulative number of times: 2 times.

[0129] The Raman spectra of Examples 1 to 3 are used to illustrate the characteristics. Figure 6 to Figure 8 The Raman spectra of the carbon black prepared in Examples 1 to 3 of the present invention are shown in Figure 1. As can be seen from the figure, the Raman spectra of the carbon black prepared in the present invention have three characteristic peaks, namely, D Raman scattering peak, G Raman scattering peak and 2D Raman scattering peak. The carbon black prepared in Examples 1 to 3 has a peak at 2648-2660 cm -1 The full width at half maximum of the 2D Raman scattering peaks in the range of -1 、80cm -1 、85cm -1 Among them, the 2D Raman scattering peak is a symmetrical sharp single peak, and the peak position of the 2D Raman scattering peak is lower than that of general bulk graphite (about 2710cm -1 ) shifts to the left, which is the characteristic peak of graphene that is different from bulk graphite. This also proves the existence of graphene-like sheet protrusions in the carbon black of the present invention, which is consistent with the TEM result.

[0130] In addition, the 2D Raman scattering peak has a great correlation with the graphene layer structure and stacking mode. Generally, the fewer the number of graphene layers, the sharper and more symmetrical the 2D Raman scattering peak. The 2D Raman scattering peak of the carbon black prepared by the present invention has symmetry, and I 2D / I G The I of conventional high-quality single-layer graphene is 0.55, 0.87, and 0.70 respectively. 2D / I G As the ratio decreases, the number of graphene layers increases, but the Raman scattering of the graphite layer on the surface of the carbon black sphere is removed to contribute to the G peak of the Raman spectrum of the carbon black. 2D / I G is 0.55-0.87, indicating that the number of graphene-like protrusions in the carbon black is small, which is consistent with the TEM results. 2D / I G When it is 0.55 to 0.87, the graphene-like sheet protrusions of carbon black can show the unique flexibility of the graphene sheet, and can improve the surface contact between the graphene-like sheet protrusions and between the graphene-like sheet protrusions and the carbon black spheres, so that the carbon black can have excellent conductivity.

[0131] Further calculations were made through Raman spectra, and the La of the carbon blacks prepared in Examples 1 to 3 were This indicates that the carbon black prepared by the present invention has a higher degree of graphitization.

[0132] At the same time, the degree of graphitization of carbon black is further characterized by crystallinity. It is measured by Raman spectroscopy that the crystallinity of the carbon black prepared in specific Examples 1 to 3 is 46%, 52%, and 42%, respectively, which further illustrates that the carbon black prepared by the present invention can obtain a high degree of graphitization. Therefore, when it is used as a conductive material for a battery, its high conductivity can improve the battery capacity and electrical characteristics.

[0133] The characteristic information of carbon black of different embodiments and comparative examples of the present invention obtained according to Raman spectroscopy is shown in Table 3.

[0134] Table 3 Characteristic information of different embodiments and comparative examples

[0135]

[0136] As shown in Table 3, the carbon black of the present invention further satisfies the Raman spectrum with an excitation wavelength of 532 nm at 2648-2660 cm -1 The full width at half maximum of the 2D Raman scattering peak in the range of 80 to 90 cm -1 ; The ratio of the peak intensity of the 2D Raman scattering peak to the peak intensity of the G Raman scattering peak is 0.55 to 0.87; La is The crystallinity is 42% to 52%, indicating that the number of graphene layers, stacking mode and edge structure in the graphene-like sheet protrusions in the carbon black of the present invention meet certain conditions, which is beneficial to further improve the conductive properties of the carbon black.

[0137] Experimental Example 3

[0138] The BET specific surface area of ​​the carbon black of different embodiments and comparative examples was tested according to GB / T19587-2004; the powder resistivity of the carbon black of different embodiments and comparative examples was tested using a semiconductor powder resistivity tester (model FZ-2006), and the test sample was prepared using a mold under a pressure of 83.5 kg; the DBP oil absorption value of the carbon black of different embodiments and comparative examples was determined using the standard method of "GB / T 3780.2-2017 Carbon Black Part 2: Determination of Oil Absorption Value", and the specific test results are shown in Table 4.

[0139] Table 4 Test results of BET specific surface area, powder resistivity and DBP oil absorption value of different embodiments and comparative examples

[0140]

[0141]

[0142] As can be seen from Table 4, the carbon black of the present invention has a high BET specific surface area, indicating that it has a developed porous structure, which increases the number of contact points between it and other substances such as active substances in the electrode, and can give full play to the conductive properties of carbon black. In addition, the powder resistivity of the carbon black of the present invention is low, indicating that its conductivity is significantly improved compared with the same type of conductive material carbon black. The void volume inside the carbon black aggregate can be characterized by the DBP oil absorption value. The carbon black of the present invention has a high DBP oil absorption value, indicating that the carbon black of the present invention has a developed chain branch structure and a developed conductive network.

[0143] The powder resistivity of the electrode slurries in Example 4 and Comparative Examples 1 to 2 was further tested. The specific testing method includes: drying each electrode slurry at 130° C. under vacuum conditions for 3 h and crushing to obtain powder; then using a semiconductor powder resistivity tester (model FZ-2006) for testing. The test sample was prepared using a mold under a pressure of 83.5 kg. The test results are shown in Table 5.

[0144] Table 5 Powder resistivity of different electrode slurries

[0145]

[0146] From the above test results, it can be seen that the powder resistivity of the electrode material prepared by using the carbon black of the present invention is significantly lower than that of the electrode material prepared by using the carbon black of the comparative example. It can be seen that the carbon black of the present invention has a graphene sheet-like protrusion structure, which helps to increase the surface contact between the active material and the carbon black and between the carbon blacks, thereby significantly improving the conductivity of the slurry and the electrode material.

[0147] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. Carbon black having high electrical conductivity, characterized in that The average particle size of the primary particles of the carbon black is 20 to 40 nm; The primary particles of carbon black include a sphere and graphene-like protrusions located on the surface of the sphere; the graphene-like protrusions are in-situ grown on the surface of the sphere; The Raman spectrum of the carbon black at an excitation wavelength of 532 nm satisfies the following characteristics: (1) 2648-2660 cm -1 The full width at half maximum of the 2D Raman scattering peak in the range of 80 to 90 cm -1 ; (2) The ratio of the peak intensity of the 2D Raman scattering peak to the peak intensity of the G Raman scattering peak is 0.55 to 0.87; (3) The Raman crystallite plane size is 32 to 51 Å; The maximum distance between any two points in the graphene-like protrusion is 10 to 50 nm; The crystallinity of the carbon black is 42% to 52%.

2. The carbon black having high conductivity according to claim 1, characterized in that The graphene-like sheet protrusions are multi-layer graphene.

3. The carbon black having high conductivity according to claim 2, characterized in that The number of layers of the multilayer graphene is ≤10.

4. The carbon black having high conductivity according to claim 2, characterized in that The number of layers of the multilayer graphene is 2 to 8.

5. The carbon black having high conductivity according to claim 1, characterized in that The carbon black is acetylene black.

6. The carbon black having high conductivity according to claim 1, characterized in that The BET specific surface area of ​​the carbon black is 65 to 180 m 2 / g; DBP oil absorption value is 235~375cm 3 / 100g.

7. The carbon black having high conductivity according to claim 1, characterized in that The crystallinity of the carbon black is 46% to 52%.

8. The carbon black having high conductivity according to claim 1, characterized in that The powder resistivity of the carbon black is 0.13 to 0.206 Ω / cm.

9. The method for preparing carbon black having high conductivity according to any one of claims 1 to 8, characterized in that: The steps include: Acetylene and methane undergo thermal cracking reaction in a hydrogen-containing and air-isolated environment to form carbon black; The flow rates of acetylene, methane and hydrogen are regulated so that the molar ratio of H to C in the thermal cracking reaction zone is greater than 1.

10. The preparation method according to claim 9, characterized in that: The molar ratio of H to C in the thermal cracking reaction zone is 2 to 3.

11. The preparation method according to claim 9, characterized in that: The gas flow directions of the acetylene and the methane are opposite; the gas flow direction of the hydrogen is arranged at an angle to the gas flow directions of the acetylene and the methane.

12. The preparation method according to claim 11, characterized in that: The angle is 45° to 60°.

13. The preparation method according to claim 9, characterized in that: The equipment for implementing the preparation method comprises: a cracking furnace body, a reaction chamber is formed inside the cracking furnace body; The cracking furnace body is provided with two nozzles communicating with the reaction chamber, and the cracking furnace body is formed with a furnace head corresponding to the two nozzles; the furnace head is provided with at least one gas introduction pipe communicating with the reaction chamber; The two nozzles include a first nozzle and a second nozzle.

14. The preparation method according to claim 13, characterized in that: The device comprises two gas introduction pipes, which are arranged opposite to each other on both sides of the furnace head.

15. The preparation method according to claim 13, characterized in that: The central axis of the gas inlet pipe is arranged at an angle with the central axis of the furnace head.

16. The preparation method according to claim 15, characterized in that: The angle is 30° to 45°.

17. An electrode, characterized in that: The carbon black comprises the carbon black described in any one of claims 1 to 8 or the carbon black prepared by the preparation method described in any one of claims 9 to 12.

18. A secondary battery, characterized in that: It comprises a positive electrode, a negative electrode, an electrolyte and a separator; at least one of the positive electrode and the negative electrode is the electrode according to claim 17.

Citation Information

Patent Citations

  • Three-dimensional graphene powder material and preparation method thereof

    CN110518251A

  • Carbon black and its production and use

    JP1995228796A

Cited By

  • Highly conductive carbon black, preparation method therefor, device, electrode, and secondary battery

    EP4806956A1